Angiogenesis inhibitors and symptomatic anal ulcers in metastatic colorectal cancer patients**. (4th March 2018) - Bergamo, Francesca; Lonardi, Sara; Salmaso, Beatrice; Lacognata, Carmelo; Battaglin, Francesca; Cavallin, Francesco; Saadeh, Luca; Murgioni, Sabina; Caruso, Antonino; Aliberti, Camillo; Zagonel, Vittorina; Castoro, Carlo; et al.
Abstract: Background: Angiogenesis inhibitors are a standard first-line treatment for metastatic colorectal cancer. Anal canal pain is a common adverse event, but its cause has never been described. The aim of the study was to evaluate the association between the use of angiogenesis inhibitors and symptomatic anal ulcer development. Methods: This retrospective cohort study included all 601 consecutive metastatic colorectal cancer patients undergoing first line treatment from January 2010 to June 2016 at the Veneto Institute of Oncology. Details about patient characteristics, treatment and proctology reports were retrieved and compared. Vascularization of the anal canal was evaluated with contrast MRI. Results: Fifty out of 601 patients reported perianal complaints during treatment and underwent proctologic evaluation. Among those, 16 were found to have an anal ulcer. Symptomatic anal ulcers occurred only in patients receiving bevacizumab (4.2% vs. 0% with other regimens, p  = .009). The peak incidence was 4–8 weeks after treatment start. Vascularization of anal canal was significantly lower in patients treated with bevacizumab ( p  = .03). Hypertension and hemorrhoids were associated with a lower risk of anal ulcer occurrence ( p  = .009 and p  = .036). Pain intensity was severe. All attempts at symptomatic treatment only led to transient benefit. The absence of symptomatic ulcers was protective against earlier permanent discontinuation of treatment (HR = .22, 95%CI: 0.04–0.62). Conclusions: The development of symptomatic anal ulcers in patients receiving angiogenesis inhibitor is a common adverse event which can compromise the continuation of cancer therapy. We recommend an early proctologic evaluation in case of anal symptoms with the aim to prevent and timely manage such complication.